2001
DOI: 10.1002/1522-2683(200109)22:17<3677::aid-elps3677>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Capillary sodium dodecyl sulfate-DALT electrophoresis of proteins in a single human cancer cell

Abstract: Capillary Sodium dodlecyl sulfate (SDS)-DALT an (abbreviation for Dalton) electrophoresis was applied to analysis of proteins in single HT29 human colon adenocarcinoma cells. A vacuum pulse was employed to introduce a single cell into the coated capillary. Once the cell was lysed, proteins were denatured with SDS, fluorescantly labeled with 3-(2-furoyl)-quinoline-2-carboxaldehyde (FQ), and then separated by using 8% pullulan as the sieving matrix. This method offers a few advantages for single-cell protein ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
56
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18] Unfortunately, one disadvantage of CE as a tool for chemical cytometry is its relatively low throughput, typically 5-35 cells per day. 10,11,17,19 In order to fully characterize many biological attributes, the analysis of hundreds to thousands of cells is often necessary to obtain statistically relevant data. For example, 100's of Xenopus oocytes were analyzed to reveal the on/off switch of MAP kinases and 1000's of rat basophilic leukemia cells were analyzed to deconvolute specific signaling mechanisms of protein kinase C. 20,21 In order to improve the low throughput of the CE analysis of adherent cells, and increase the feasibility of implementing this technique routinely in evaluating cellular attributes, new highthroughput methods are needed for chemical cytometry performed by CE.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] Unfortunately, one disadvantage of CE as a tool for chemical cytometry is its relatively low throughput, typically 5-35 cells per day. 10,11,17,19 In order to fully characterize many biological attributes, the analysis of hundreds to thousands of cells is often necessary to obtain statistically relevant data. For example, 100's of Xenopus oocytes were analyzed to reveal the on/off switch of MAP kinases and 1000's of rat basophilic leukemia cells were analyzed to deconvolute specific signaling mechanisms of protein kinase C. 20,21 In order to improve the low throughput of the CE analysis of adherent cells, and increase the feasibility of implementing this technique routinely in evaluating cellular attributes, new highthroughput methods are needed for chemical cytometry performed by CE.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we are interested in developing a technology to allow the study of protein expression in single somatic cells. Currently, LIF is the most common detector for CE analysis of proteins in single cells [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Pullulan was demonstrated in CE-format SDS protein electrophoresis assays. 96,101 The low viscosity of pullulan was a chief selection criteria.…”
mentioning
confidence: 99%
“…96 An 8% pullulan sieving matrix yielded similar separation performance to that obtained by slabgel SDS-PAGE. 45 Griebel et al reported a 2D gel capillary electrophoresis (2D-CGE) in a PMMA microuidic chip. 46 The rst dimension was isoelectric focusing (IEF) using an immobilized pH gradient (IPG).…”
mentioning
confidence: 99%